2000
DOI: 10.1084/jem.191.4.661
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tumor Surveillance by Natural Killer (Nk) and Nkt Cells

Abstract: Natural tumor surveillance capabilities of the host were investigated in six different mouse tumor models where endogenous interleukin (IL)-12 does or does not dictate the efficiency of the innate immune response. Gene-targeted and lymphocyte subset–depleted mice were used to establish the relative importance of natural killer (NK) and NK1.1+ T (NKT) cells in protection from tumor initiation and metastasis. In the models examined, CD3− NK cells were responsible for tumor rejection and protection from metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
520
1
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 719 publications
(544 citation statements)
references
References 47 publications
17
520
1
6
Order By: Relevance
“…iNKT cells are abundant in the liver and rapidly secrete large amounts of immunoregulatory cytokines such as IFN-g and IL-4 after stimulation through their TCR [35][36][37][38][39][40]. Administration of a-GalCer to mice causes rapid release of various cytokines from iNKT cells, which participate in the regulation of various diseases, including tumor rejection and prevention of autoimmune diseases [41][42][43][44][45][46].Although a-GalCer can enhance host resistance against some microbial pathogens [47-55], it remains elusive whether a-GalCer enhances protective immunity against intracellular bacteria.We have recently shown that listeriosis is ameliorated in iNKT-cell-deficient mice [56]. This finding argues against a protective role of iNKT cells in listeriosis.…”
mentioning
confidence: 99%
“…iNKT cells are abundant in the liver and rapidly secrete large amounts of immunoregulatory cytokines such as IFN-g and IL-4 after stimulation through their TCR [35][36][37][38][39][40]. Administration of a-GalCer to mice causes rapid release of various cytokines from iNKT cells, which participate in the regulation of various diseases, including tumor rejection and prevention of autoimmune diseases [41][42][43][44][45][46].Although a-GalCer can enhance host resistance against some microbial pathogens [47-55], it remains elusive whether a-GalCer enhances protective immunity against intracellular bacteria.We have recently shown that listeriosis is ameliorated in iNKT-cell-deficient mice [56]. This finding argues against a protective role of iNKT cells in listeriosis.…”
mentioning
confidence: 99%
“…Identification of the NKT cell subsets that might specialise in Th1 versus Th2 functions has not been thoroughly investigated. The secretion of Th1 and Th2 cytokines by NKT cells is thought to underlie the regulatory properties of these cells (5,6), which suggests a flexible role for NKT cells in immunoregulation, although a clear difference in cytokine production between NKT cell subsets cannot be resolved at this time. Although expression profiles of Th1/Th2 cytokines between mice and humans differ, the question remains as to how these cytokines lead to a regulated immune response in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…To test this point, mice were inoculated with B16F10 melanoma cells which are known to be controlled by NK cells. 27,28 While C57BL/6, C57BL/6 × Ly5.1 C14R and Ly5.1 (Jax, 2017) mice were able to largely control tumor growth as measured by the number of primary lung tumors 14 days after tumor inoculation (Figure 4C and D), mice that expressed the NKp46 C14R single point mutation developed significantly more lung metastases, a condition that was accompanied by respiratory distress. These mice also presented metastases in other organs such as the kidney, liver and bone marrow (SI Appendix, Figure S5 D ), a phenotype which was similar to that observed in Mcl-1 fl/fl Ncr1 iCre mice in which NCR + cells are conditionally ablated 29 (Figure 4C and D and SI Appendix, Figure S5D).…”
Section: Resultsmentioning
confidence: 99%